MEV Energy Electrostatic Accelerator Ion Beam Emittance Measurement - I.G. Ignat’ev; M.I. Zakharets; S.V. Kolinko; D.P. Shulha (Журнал нано- та електронної фізики)
The testing equipment was designed, manufactured and tried out permitting measurements of total current, current profile and emittance of an ion beam extracted from the ion beam. MeV energy electrostatic accelerator ion H + beam emittance measurement results are presented.